Mapping Leisure in the Philippines - Enverga, Manuel R, III (Archīum Ateneo, 2018)
On 14 July 2011, the cinemas of several large shopping malls in the Philippines stayed open to show the second instalment of Harry Potter and the Deathly Hallows, which was being released simultaneously throughout the world. Despite the late hour, people lined up and watched in order to be one of the first people in the world to see the film, not just in the country, but, owing to the Philippines’ advanced time zone, also throughout the world. Though they may not have consciously thought it at the time, their participation in a midnight screening of a blockbuster movie like the eighth, and final, Harry Potter film was a form of participation in a leisure activity that would occur at a global scale. In a small way, they were thus participating in globalization, since fans throughout the world would be doing the same. In addition, it is global trade and consumption, and the transportation and information networks that they rely on, that have allowed the popularity of a cultural product like Harry Potter.